A specular relationship: notes on the imaginary dimension of architecture - Leitão, Lúcia (Risco - Journal of Architecture and Urbanism, 2011)
This text aims at calling attention to the specular dimention of the relationship established between the subject and the constructed space. This text works with the hypothesis that from an experience, which is by definition subjective, architecture offers itself as a mirror, and, in doing so, performs an essential role in the constitution of the subject. The theoretical reference comes from architecture (Quatremère de Quincy) and of psychoanalysis (Lacan). The text argues that the imaginary dimension of architecture opens up a field of research on the theory of architecture that is as incipient as it is fascinating.